Gambaran Pengetahuan Remaja Putri tentang Tablet Tambah Darah untuk Pencegahan Anemia dan Kesehatan Reproduksi di SMAN 15 Kota Bekasi - Aldhya Nadhira Lokanata; Nenny Hendajany; Dedy Agus Purwanto; Taufiq Supriadi; Amiruddin Setiawan (PT. Hasba Edukasi Mandiri, 2026)
Anemia is a global health problem commonly experienced by adolescent girls, with serious implications for reproductive health and future pregnancies. This study aims to describe adolescent girls' knowledge about Iron Supplement Tablets (TTD) in preventing anemia and reproductive health. This descriptive-analytic study was conducted at SMAN 15 Bekasi City with a sample of 50 female students selected by purposive random sampling. Data were collected through an online questionnaire and analyzed descriptively. Results showed that all respondents (100%) knew the definition of anemia, 94% knew that the main cause of anemia is lack of iron intake, and 100% knew anemia symptoms such as difficulty concentrating and frequent drowsiness. 100% knew iron-rich foods, and 96% agreed to consume iron supplements during menstruation. However, only 46% knew all the long-term impacts of anemia. Conclusion: Adolescent girls' knowledge about anemia and TTD is good, but understanding of long-term impacts still needs to be improved through more intensive education.